PENGARUH INKLUSI KEUANGAN DI ERA EKONOMI DIGITAL DALAM MENINGKATKAN PERTUMBUHAN EKONOMI - Pramaswara, Muhammad Alifanda; Moh. Athoillah (Journal of Development Economic and Social Studies, 2023)
Financial inclusion has become one of the national economic recovery (PEN) policies. Through financial services that are transformed into digital-based services, it is expected to boost growth. This study aims to find out the relationship between financial inclusion and economic growth. The convergence growth model were the approach used in this research  to see how financial inclusion and information communication technology (ICT) indicators affect economic growth in 34 provinces in Indonesia in 2015-2021. The data used comes from the Indonesian Central Bureau of Statistics (BPS) and the Financial Services Authority (OJK). The results of this study indicate that financial inclusion has a significant effect on growth. Third party funds and savings ratios have a significant effect, while bank branch offices and mobile phone users do not have a significant effect. The estimation results also show that the less developed regions catch up with the more developed regions.